Better = faster? Explaining citizens' desired speed of European integration. Issue 1 (2nd January 2017) - Malang, Thomas
Abstract: Is the public EU membership evaluation similar to the support for further integration or different? Starting from the assumption that the EU is – compared to stable nation states – still a 'polity in the making', the paper answers the question which factors can explain the desired speed of integration. I first hypothesise that the standard economic, political and cultural explanations have the same effect for the (prospective) desired speed of integration than they have for the (retrospective) membership evaluation analysed in previous studies. Additionally, I develop two temporal explanations specifically for the explanation of future support. The results on the basis of Eurobarometerdata from 2008 suggest that the canonical economic and political theories work only for the explanation of the membership evaluation and not for the desired speed.